One-pot synthesis of magnetic chitosan/iron oxide bio-nanocomposite hydrogel beads as drug delivery systems. Issue 4 (2nd October 2021) - Barkhordari, S.; Alizadeh, A.; Yadollahi, M.; Namazi, H.
ABSTRACT: In this research, a novel dual-responsive supermagnetic chitosan/iron oxide nanocomposite hydrogel beads (CH/MION) was prepared using sodium tripolyphosphate (STPP) as cross linking agent. The prepared CH/MION hydrogel was systematically characterized by Fourier transforminfrared spectroscopy (FT-IR), scanning electron microscopy (SEM) X-ray diffraction (XRD), and vibrating sample magnetometer (VSM). In addition, the CH/MION hydrogel exhibits favorable swelling properties that are sensitive to pH, and external magnetic field (EMF). The drug release behavior of the prepared hydrogel under EMF, and different pHs was also studied. The obtained hydrogel showed considerable temperature, pH, and EMF sensitivity for the in vitro release of Doxorubicin (DOX).These results suggested that the CH/MION hydrogel beads could be a promising candidate for drug delivery applications.